Influence of the active region structure of the resonant tunneling diode on the critical points of its current-voltage characteristic - Yatsun, К.S. (Radiotekhnika, 2022)
The article proposes a study of the effect of the structure of the active region of a resonant tunneling diode on the critical points of its current-voltage characteristic. The basic configuration of a resonant tunneling diode, which is a structure of a quantum well with a nanometer-sized double barrier including two contacts, and a region with strongly doped contacts made of a semiconductor with a relatively small band gap, is disclosed and illustrated. It is emphasized that since the characteristic dimensions of the structure of the quantum well with a double barrier are comparable to the wavelengths of electrons, the wave nature of electrons leads to such quantum phenomena as interference, tunneling, energy quantization, etc. the double barrier causes resonant tunneling phenomena, which form the basis for the operation of the resonant-tunneling diode. It is emphasized that repeated reflection causes destructive or constructive interference depending on the wavelength of a particular electron. For electrons with a certain wavelength that promotes constructive interference, a transfer probability close to unity can be found at energies corresponding to these wavelengths. The modification of the active region of the resonant tunnel diode with a barrier height of 0.3 - 0.4 eV is mathematically substantiated. The dependence of the transmission coefficient is found by solving the Schrödinger equation in one electron approximation without taking into account the scattering effects. The calculation of the volt-ampere characteristic of the resonant-tunnel diode was performed at temperatures of 100 and 300 K. The given volt-ampere characteristics were obtained without taking into account the effects of electron scattering. However, it should be noted that the main influencing factor is the resonant tunneling through the second level, for which the peak of the transmission coefficient is much wider and higher. However, in gallium doped arsenide, the fact of electron scattering can significantly affect the value of the transmission coefficient and the value of current. It is established that an increase in the width of quantum wells leads to a significant decrease in the densities of peak currents and valley currents, and an increase in the width of potential barriers leads to a slight decrease in the current density of the first peak and current densities of the second peak and valley.